Ambulatory and inpatient procedures in the United States, 1995. - Kozak, Lola Jean.; Owings, Maria.; National Center for Health Statistics (U.S.) (U.S. Dept. of Health and Human Services, Centers for Disease Control and Prevention, National Center for Health Statistics, 1998)
Presents estimates of surgical and nonsurgical procedures performed in the United States during 1995. The report is based on data collected from the National Hospital Discharge Survey (NHDS) and the National Survey of Ambulatory Surgery (NSAS).
"March, 1998."
"By Lola Jean Kozak and Maria F. Owings"--P. 1
Includes bibliographical references (p. 12-13).
Presents estimates of surgical and nonsurgical procedures performed in the United States during 1995. The report is based on data collected from the National Hospital Discharge Survey (NHDS) and the National Survey of Ambulatory Surgery (NSAS).
Also available in PDF format via the CDC Web site. Address as of 2/3/2010http://www.cdc.gov/nchs/data/series/sr_13/sr13_135.pdf
Keywords: Patient Discharge / United States / Statistics.; Hospitalization / United States / Statistics.; Ambulatory Care / United States / Statistics.; Surgical Procedures, Operative / United States / Statistics.; Hospitals / Outpatient services / United States / Statistics.; Ambulatory surgery / United States / Statistics.